Timeliness of Financial Report Presentation in Companies Listed on Indonesia Stock Exchange - Fajar Rina Sejati; Dian Pertiwi; Riana Yuliani Marpaung (Politeknik Negeri Semarang, 2025)
This empirical research was conducted to examine and analyze the timeliness of financial report presentation in companies listed on the Indonesia Stock Exchange. The population in this study was 42 companies listed on the Indonesia Stock Exchange (IDX) that reported their 2019 annual financial reports late. Using purposive sampling, a sample of 11 companies was obtained for the 2016-2020 period. The analysis technique used was logistic regression. The results showed that profitability, leverage, company size, and company age did not affect the timeliness of financial report presentation.